Cognitive Effort, Affect, and Choice - Garbarino, Ellen C.; Edell, Julie A. (Journal of Consumer Research, 1997)
This article examines cognitive effort and its influence on choice outcomes through process-induced negative affect. We propose that an alternative that requires more cognitive effort to evaluate leads the decision maker to generate more negative affect and to choose that alternative less frequently than an alternative that is less effortful to evaluate. Two studies demonstrate that when different levels of effort are expended processing equivalent alternatives, the effort adversely affects choice of the more difficult to process alternatives. More respondents, especially those with less skill at the evaluation task, selected a brand and expressed a greater willingness to pay a premium for it when it was less effortful to evaluate. The second study shows that more negative affect was generated as the cognitive effort increased, lowering the likelihood of the difficult alternative being selected. The extent of negative affect generated was exaggerated under time pressure and increased the choice of the less difficult alternative. Although negative affect was generated, it did not influence choice when there was a clearly superior alternative.